Pelayanan Misi Holistik Memakai Media Digital - Tessy, Charles; Siligar, Ambrosius (Jurnal Teologi Kontekstual Indonesia, 2023)
The use of digital media is a current trend. This progress should be utilized in Christian mission services, especially in responding to the challenges of service in underdeveloped villages scattered throughout Indonesia. This article tries to explain the use of digital media in holistic mission services in Bambaoma village. By using ethnographic qualitative methods and also use a variety of existing literature and observations of researchers who have served in this village. The results of the study found that the use of digital media for holistic mission services in Bambaoma hamlet can be used to support teaching and training in various fields, both in the spiritual field through sermons, teaching in Sunday Schools and basic education for young children, as well as teaching ways to good farming practices and healthy lifestyles to improve the welfare of the Bamboama hamlet community holistically.